Mídia e envelhecimento feminino: transformações no corpo e implicações subjetivas - Borges, Carlise Nascimento (2012)
This research has as subject women‟s aging and the relation with their bodies, subjectivity and media. Nowadays, it‟s possible to see right models of body have been disseminate for the media, consolidating hard meanings of beauty. When the aging arrives, the woman realizes a distance from these right models, and invests frantically in search of them, becoming a compulsory chaser of displays, images and bodies, making all kind of changes to reach the model of body and youth many times unreachable. These body changes are connected with the subjectivity that is built by the media. Then the body becomes a control mechanism, which the media, in the most of times, becomes a big coupled in this process, which the society usually blame those who let themselves grow old. The research‟s purpose is comprehend how the aging woman, in the contemporary society, realizes the separation of these body and beauty standards mainly disseminated by the media, and, still, how this body subject incises in the development of their subjectivities. To this end, interviews were conducted with Goianienses women, assiduous frequenters of fitness centers, from different walks. The analysis of these interviews was related to a media analysis in order to compare the two speeches, as one perceives a spread of hegemonic patterns and behaviors of bodies permeated the live of these women.